2018
DOI: 10.1111/tmi.13087
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone interventions for tuberculosis should ensure access to mobile phones to enhance equity – a prospective, observational cohort study in Peruvian shantytowns

Abstract: ObjectivesMobile phone interventions have been advocated for tuberculosis care, but little is known about access of target populations to mobile phones. We studied mobile phone access among patients with tuberculosis, focusing on vulnerable patients and patients who later had adverse treatment outcomes.MethodsIn a prospective cohort study in Callao, Peru, we recruited and interviewed 2584 patients with tuberculosis between 2007 and 2013 and followed them until 2016 for adverse treatment outcomes using national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This can be used, alongside contact surveys where the location of contact was recorded, to estimate likely reductions in contacts. A major caveat is that those surveyed include mobile phone owners only, which may underrepresent both TB patients 98 and potentially those unable to practice physical distancing.…”
Section: Mycobacterium Tuberculosis Transmissionmentioning
confidence: 99%
“…This can be used, alongside contact surveys where the location of contact was recorded, to estimate likely reductions in contacts. A major caveat is that those surveyed include mobile phone owners only, which may underrepresent both TB patients 98 and potentially those unable to practice physical distancing.…”
Section: Mycobacterium Tuberculosis Transmissionmentioning
confidence: 99%
“…Importantly, any economic support should involve engagement with patient civil society organisations, as they have a potentially critical role in providing psychosocial support to tuberculosis-affected households, reducing stigma and discrimination [19,20]. This may harness digital technology to improve equity and efficiency, and overcome the infection control challenges associated with both tuberculosis and COVID-19 [21]. Tuberculosis-specific social protection should improve equitable access to tuberculosis care and prevention, reduce poverty-related tuberculosis risk factors, and therefore improve outcomes [22][23][24].…”
Section: Social Protection Interventionsmentioning
confidence: 99%
“… 62 52 However, a recent study from Peru highlights that, although cellphone access may be high in the general population, access may be considerably lower in patients who suffer from TB and in particular for patients with TB with poor treatment outcomes. 63 Implementation studies from high-income and middle-income countries (USA, Canada, Belarus, Mexico) have suggested that VDOT has high feasibility, 53 64–66 though some patients had to be shifted back to in-person DOT 53 and low video or audio quality sometimes made dose observation difficult. 65 67 Ingestible sensors had high feasibility in studies conducted in the USA and Mexico, with >95% of sensor signals detected after ingestion.…”
Section: Research Priorities and Existing Evidencementioning
confidence: 99%